Climate Change and its Impact on Biodiversity: Adaptive Strategies for Conservation - Hussein, Mohammed Jassim Muhammad Abdul; Jrah, Hussein Ali Hussein; mohammed, Obaida Manhal ibrahim; jasim, Noor Rasim yousif (American Journal of Biodiversity, 2024)
Biodiversity refers to the variety and composition of life on Earth. From microbes to mammals, biodiversity affects all living organisms. Therefore, it is critical for human activities and for the development of policies oriented toward conservation and protection of natural heritage and the provisioning of ecosystem services. However, biodiversity is threatened: anthropogenic climate change is expected to promote species extinction and could push a significant percentage of living organisms to extinction by 2100. Climate change triggers a broad array of direct and indirect effects on organisms and ecosystems; among others, we can find temperature increase, changes in precipitation patterns, and increases in the frequency of extreme events. Therefore, in order to dampen the negative effects of climate change on biodiversity, a new proactive attitude in species conservation is needed. Current conservation strategies must allow species to increase ecological plasticity, adaptive capacity, and, in turn, the evolutionary potential of populations. Current conservation strategies applied within regional park and reserve management must be adapted to this new perspective.